اسلامی مالیات میں سلَم اور استصناع: بنیادی تصورات اور جدید اطلاقات: Salam and Istiṣnāʻ in Islamic Finance: Classical Theories and Modern Applications - Dr. Muhammad Talha Hussain (Al Manhal Research Journal, 2024)
This research paper explores the classical and contemporary concepts of Salam and Istiṣnāʻ, two significant contracts in Islamic jurisprudence, which address deferred delivery in trade and manufacturing processes. The study examines their historical foundations in Islamic law, their principles, and their applications in traditional economic systems. It also analyses how these contracts have been adapted to meet the demands of modern finance, commerce, and industry while adhering to Sharīʻah principles. The paper delves into the operational frameworks of Salam and Istiṣnāʻ in contemporary contexts, highlighting their role in sectors such as agriculture, construction, and manufacturing. Key differences and similarities between the two contracts are discussed to provide a comprehensive understanding of their practical utility. Furthermore, the study evaluates the challenges and opportunities associated with the implementation of these contracts in modern financial systems, including their integration with Islamic banking and their contribution to socio-economic development. The findings aim to bridge the gap between classical jurisprudential interpretations and modern applications, offering insights for policymakers, financial institutions, and scholars of Islamic finance. By presenting a comparative and applied analysis, this research underscores the relevance of Salam and Istiṣnāʻ in fostering ethical and sustainable trade practices in the contemporary era.